Productivity of Waqf Funds in Indonesia: A Malmquist Index Approach on Selected Philanthropic Institutions - Mimma Maripatul Uula (SMART Insight, 2022)
The goal of this study is to use the Malmquist Productivity Index to figure out how well zakat institutions in Indonesia manage waqf funds. The objects of this study consist of six Zakat institutions in Indonesia, and the data used in this research comes from the annual reports of these institutions during the 2017–2021 period. The input variables in this study include salary expenses, operating expenses, and total assets. Meanwhile, output variables include collected waqf funds and distributed waqf. The results of the study found that the Malmquist Productivity Index (MPI) score for each Zakat institution explained that the level of productivity of Zakat institutions in managing waqf funds fluctuated from year to year. In general, the level of work done by zakat institutions has gone down. This is because efficiency and technology have changed. Analysis during the COVID-19 pandemic found that the productivity of Zakat institutions managing waqf funds before the pandemic had a higher level of productivity than during the pandemic. And analysis of the Malmquist Index quadrant shows that Zakat Institutions managing waqf funds dominate in quadrant 3, with a total of 3 Zakat Institutions, and quadrant 4, with the same number of Zakat Institutions, namely 3 institutions.